Petrographic, whole-rock geochemical and δ34S isotope characterisation of the Middelvlei Reef in the Witwatersrand Basin - Mooa, Phuthanang Faith (University of the Witwatersrand, Johannesburg, 2025)
Gold is still one of the greatest sought-after metals in the world. The Witwatersrand Basin in South Africa has historically been a key gold metallogenic province. However, the extensive exploitation of the Mesoarchean Witwatersrand Basin has led to the exhaustion of many of its primary, regionally persistent orebodies known as “reefs”. Consequently, the exploration of secondary composite orebodies within the Witwatersrand Basin has become a necessity. Composite reefs, characterised by multiple auriferous conglomerate beds, present significant opportunities for continued gold recovery in the Witwatersrand Basin. However, their origin and gold content have often been overlooked due to their restricted or localised mineralisation extent and lower gold tenor compared to thin conglomerate beds and goldrich carbon seams. The Middelvlei Reef serves as an exemplary composite reef, that is found at the bottom of the Central Rand Group in the Witwatersrand Basin. The Middelvlei Reef, along with its counterparts such as the Elsburg Reefs, exhibits distinctive features where gold is frequently interlinked with multi-stacked auriferous and pyrite-rich conglomerates. The quartz-pebble conglomerates of the Middelvlei Reef are noted for their exceptional pyrite richness, relatively moderate gold grades (i.e., <5 g/t), and thin, alternating multicycle conglomerates, rendering them a complex subject for gold-bearing formation studies. This research focuses on the morphology and chemical composition of pyrite grains within the Middelvlei Reef to explain the depositional environment through comprehensive trace element chemistry and sulphur isotope (δ34S) analysis. The study identifies various pyrite morphologies based on textural distinctions, classifying them into detrital and authigenic types. Detrital pyrite can be classified as massive, inclusion-bearing (random, planarlaminated, concentrically laminated, and micro-spherical), and coarsely crystalline detrital pyrite. Authigenic pyrite is classified into euhedral/subhedral, overgrowth, infill, aggregates, and pseudo-morphic pyrite. Conventional and advanced analytical techniques such as reflected light optical microscopy, scanning electron microscopy and energy dispersive X-ray spectroscopy (SEM-EDS), Tescan Integrated Mineral Analyser (TIMA), electron-probe microanalyses (EPMA), laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS), and virtual secondary ions mass spectrometry (vSIMS) were employed to investigate the in-situ trace element and δ34S composition of pyrite grains. Proxies such as Au, Au/As ratios, Co/Ni ratios, Ni, and Mo/Ni ratios were used to infer the process of gold enrichment in the Middelvlei Reef. Detrital pyrite grains are characterised by low Co/Ni (1.51 ppm) and high Au contents (3.05 ppm). Contrarily, high Co/Ni (29.96 ppm) and low Au (0.15 ppm) concentrations imply authigenic pyrite grains. The elevated Mo/Ni ratios (0.005 ppm) in these pyrite grains indicate a source from felsic to mafic rocks within the granitoid-greenstone belts of the Kaapvaal Craton. Sulphur isotopic analyses from vSIMS reveal a broad range of δ34S values (-15.39 to +38.25 ‰.) in the pyrite grains of the Middelvlei Reef, suggesting multiple sources that include localised sulphurous pools and photochemical reactions. The broad range of high positive (+38.25 ‰) and negative (-15.39 ‰) δ!"S values are attributed to the high amounts of inclusions observed within the respective grains. Clusters of positive δ34S values (-6.32 to +25.27 ‰) observed in detrital pyrite grains imply erosion of sedimentary deposits, whereas low δ34S values (-2.18 to +3.87 ‰) in authigenic pyrite grains point towards metamorphic and hydrothermal fluid sources. These findings suggest that the composite Middelvlei Reef was formed in a combination of high to low-energy braided riverine environments that allowed the accumulation of large sulphide group minerals, which were reworked into auriferous conglomerate channels. Pyrite morphology, chemistry, and isotopic composition indicate that the detrital pyrite grains were generated by a combination of sedimentary and diagenetic processes, while the authigenic pyrite grains recorded fluid mobilisation evidence and multiple re-deposition processes. Detrital pyrite, which is a fingerprint of the composite Middelvlei Reef, was created by erosion and reworking of diagenetic pyrite. This complex process resulted in the accumulation of fine-grained gold within various pyrite grains, alongside other metals like As, Ag, Cu, Ni, Co, and Mo. This study provides insights into the complex depositional and post-depositional processes that have governed gold accumulation in the Middelvlei Reef, in that way laying the groundwork for future exploration and exploitation of similar composite reefs within the Witwatersrand Basin.
This dissertation submitted in fulfilment of the degree of Master of Science in Geology, to the Faculty of Science, School of Geosciences, University of the Witwatersrand, Johannesburg, 2025
Keywords: Petrographic; Middelvlei Reef; Witwatersrand Basin; Elsburg Reefs; Scanning electron microscopy; Energy dispersive X-ray spectroscopy; Tescan Integrated Mineral Analyser (TIMA); electron-probe microanalyses (EPMA); Kaapvaal Craton; UCTD; SDG-9: Industry, innovation and infrastructure; SDG-4: Quality education